Case report: A novel mutation of the CAPN3 gene in a Chinese family with limb-girdle muscular dystrophy type 2A - Feng, Wanjun; Cao, Yanyan; Ren, Ruolin; Yang, Xiaohui; Cao, Chunyan; Jiang, Hongwei; Du, Ganqin (Frontiers in Genetics, 2024)
Limb-girdle muscular dystrophy type 2A (LGMD R1 Calpain 3-Related, LGMD2A/R1), an autosomal recessive disorder, is characterized by progressive muscle weakness with a prominent presentation in the proximal limb girdle muscles. LGMD2A/R1, which is caused by variants in calcium-activated neutral proteinase 3 (CAPN3), is the most common. The present study aimed at identifying the clinically significant variants in a Chinese family with LGMD2A/R1 and exploring the genotype–phenotype correlations. Clinical symptoms, laboratory findings, and physical examinations were obtained. Genomic DNA was extracted from the peripheral blood samples of this family. Whole-exome sequencing (WES) and Sanger sequencing were used to explore and validate the pathogenic genes. In this study, the proband and his sister, who had two identical mutations in the CAPN3 gene sequence, exhibited diverse clinical features, including disease onset and progression. The mutation c.2120 A>G (p. D707G) is pathogenic and has been reported in the Human Gene Mutation Database (HGMD) and the ClinVar database. c.1783-72 C>G may be a novel pathogenic mutation of LGMD2A/R1 based on the American College of Medical Genetics (ACMG) guidelines, which widens the gene variant pool in CAPN3 and improves diagnosis and genetic counseling.